Genetic Analysis of Multiple Loci Suggests that Mutations in the Pneumocystis carinii f. sp. hominis Dihydropteroate Synthase Gene Arose Independently in Multiple Strains - Ma, Liang (American Society for Microbiology, 2001)
To determine if mutations in the dihydropteroate synthase (DHPS) gene of Pneumocystis carinii f. sp. hominis arose in a single strain that was subsequently widely disseminated, we examined four genomic regions of 22 P. carinii clinical isolates selected based on the absence or presence of mutations in the DHPS gene. By single-strand conformation polymorphism and DNA sequencing, we found varying genotypes for each of the four regions in isolates with DHPS mutations, suggesting that these mutations occurred independently in multiple strains of P. carinii. This suggests that exposure to sulfa will select for these mutations in diverse strains.